RISK ASSESSMENT WORK OF GRINDING IN UNIT FABRICATION PT. OMETRACO ARYA SAMANTA SURABAYA - Ade Intan Puspita Sari; Mulyono S.KM., M.Kes (Universitas Airlangga, 2020)
Fabrication Unit is a work area which there are processes of production activities of various kinds of work. Many types of work carried out in fabrication unit have risk that can lead to accidents. One of the types job in fabrication unit is grinding. Process in grinding can not be separated from potential hazards and risks that must be controlled to minimize the occurrence of accidents. This study intend to assess the risk on grinding in fabrication unit of PT. Ometraco Arya Samnta Surabaya. This was an observational descriptive study with cross-sectional design. Primary data obtained through interviews and observations whereas secondaray data collected from the company. Based on the result of the study, there were 21 hazards in grinding job that can be classified into 13 low risks, 5 medium risks, and 3 high risks. The high risks were the wheel rotation of grinding machine, grinding sparks, and falling material.Keywords: grinding, hazard identification, risk assessment